Reconstructing Copyright Protection for Artificial Intelligence-Generated Works - Bernard Nainggolan; Suwarno Suwarno; Keisha Dearin Dafa (Unissula, 2026)
The development of Generative Artificial Intelligence (AI) has transformed the process of intellectual creation and raised issues regarding authorship and copyright ownership. However, Law Number 28 of 2014 concerning Copyright is still based on the human authorship paradigm and therefore does not provide legal certainty for works produced with the help of AI. This study aims to analyze the adequacy of legal protection for AI works, identify weaknesses in the concept of creator in Indonesian copyright law, and formulate a Human-Centered Copyright Ownership model. The study uses a normative legal method with a statutory, conceptual, comparative, and case approach through an analysis of laws and regulations, international instruments, court decisions, doctrines, and scientific literature. The results of the study indicate that Indonesian copyright law still experiences a normative vacuum regarding the ownership of AI works and therefore is unable to provide legal certainty. As a novelty, this study offers a Human-Centered Copyright Ownership model that positions AI as a creative tool, while copyright ownership is determined based on substantial human creative contribution. This model provides more objective normative parameters for determining creators and copyright holders and serves as a basis for reforming the Copyright Law to achieve a balance between protecting human creativity, legal certainty, and technological innovation.